Atriyal Fibrilasyon Tanı ve Tedavisine Güncel Yaklaşım - Ulun, Büşra; Kaya, Ahmet Ferhat; Söner, Serdar; Günay Polatkan, Şeyda; Çetin, Elif; Hiçyılmaz, Nihat; Koç Ay, Esra; Kayan, Fethullah; Pehlivan, Mine Büşra; Kaya, Çağlar; Yüksel, Gizem; Kartal, Yiğit Can; et al. (2023)
-